장애인 자녀를 둔 부모의 주관적 건강수준이 우울에 미치는 영향에서 자아존중감의 조절효과 분석: 성별 차이를 중심으로 - 김지연(Jiyeon Kim); 손애리(Aeree Sohn) (보건교육건강증진학회지, 2024)
Objectives: This study aimed to examine how depression moderates the effect of subjective health on self-esteem among parents of children with disabilities. Methods: We analyzed data from 1,914 parents (713 fathers and 1,201 mothers) from the fourth year of the Disability and Life Dynamics Panel. Hypothesis testing was conducted using SPSS 26.0 and Process Macro, specifically Process Macro Model 1 to test the moderating effect. Results: Depression significantly moderated the effect of subjective health on self-esteem in the overall and the paternal group, but not in the maternal group. Conclusion: The findings suggest that gender differences should be considered when developing programs to support the psychological well-being of parents of children with disabilities. Fathers exhibit higher self-esteem, whereas mothers have lower subjective health, lower self-esteem, and higher depression rates. These differences should be considered when providing programs to support their psychological well-being. KCI Citation Count: 0